Fiscal Effects of Monetary Seigniorage: A Case Study of Pakistan (The Pakistan Development Review, 1994)
The effects of monetary policy on key macro variables have been studied in the literature. In Pakistan most of these studies concentrate on exploring the interdependence of money supply, national income, inflation etc.1 One important, but neglected issue of monetary policy, is its fiscal effects. The fiscal and monetary authorities being parts of the total economic policy machinery, the role of monetary instruments in achieving fiscal objective should not be ignored. In countries like Pakistan where the central bank is under direct control of the government, fiscal policy is often made under the assumption that the monetary policy will be adjusted accordingly.2 There are a number of ways in which monetary policy may lead to fulfilment of some fiscal objectives. These include devaluation, change in interest rate and change in monetary base.